OPTIMALISASI MANAJEMEN SARANA DAN PRA SARANA DALAM MENINGKATKAN EFEKTIVITAS PEMBELAJARAN DI SEKOLAH MENENGAH KEJURUAN (SMK) BINA PUTRA MANDIRI PARUNG PANJANG BOGOR - Rahmayanti Rahmayanti; Manaratul Masropah; Zahra Maulida Kamila; Suhestiyah Suhestiyah; Hasan Basri (STKIP Pesisir Selatan, 2026)
Objective: This study aims to analyze the optimization of facilities and infrastructure management in improving the effectiveness of learning at SMK Bina Putra Mandiri Parung Panjang Bogor. Facilities and infrastructure are important components in supporting the teaching and learning process, especially in vocational schools that emphasize practical learning and skill development. This research used a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The research subjects consisted of the principal, vice principal of facilities and infrastructure, teachers, administrative staff, and student. The data analysis technique used was the interactive analysis model of Miles and Huberman, which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that the management of facilities and infrastructure at SMK Bina Putra Mandiri Parung Panjang Bogor has been implemented through systematic planning, procurement, utilization, maintenance, inventory, and supervision processes. The availability of classrooms, computer laboratories, internet networks, learning media, libraries, and practical equipment has contributed positively to improving the effectiveness of learning. Students become more active, motivated, and able to understand learning materials better through practice-based and technology-supported learning.